Processing of Crude Palm Oil and Testing of Free Fatty Acid (FFA) to Control the Quality of CPO Oil at PT. Thanks to Palm Oil Sukamaju - Finurti, Elly; Yusfarani, Delia; Harfian, Binar Azwar Anas (Universitas Ahmad Dahlan, 2024)
The purpose of this study was to determine the analysis of the quality control quality of Free Faty Acid CPO oil at PT. BSS Sukamaju. The method used in analyzing the FFA of Crude Palm Oil is the volumetric titration method using 0.1046 standard solution as the titre, Phenolpthalein as an indicator and a mixture of isopropylalcohol as the solvent which was observed for 5 days. The average FFA results obtained on September 25, 2021 to September 29, 2021 are 3.8% with a max standard of 5%, and the moisture observation results get an average of 0.13% with a max standard of 0.20%. While the results of the observation of dirt with an average of 0.0178% with a max standard of 0.02%. Thus, as a measure of quality standards in international trade, FFA is set at 5%, which means that PT. BSS has met quality standards in international trade. Quality control control that is carried out is very influential in product quality so that it can affect revenue because the selling value in marketing is very dependent on the quality or quality of the CPO.